1990
DOI: 10.1161/01.res.67.2.490
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relation between myocardial contractility and energy metabolism during and following brief coronary occlusion in the pig.

Abstract: Changes in high-energy phosphate metabolism may be important in the regulation of myocardial contractile function during ischemia. This study sought to determine the dynamic relation between myocardial contractile function and high-energy phosphate metabolism during and following brief (24-second) Because of the limited temporal resolution of metabolic measurements made by direct biochemical techniques or by nuclear magnetic resonance (NMR) spectroscopy, most of the data supporting these hypotheses in intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…This phenomenon can be attributed to the fact that ATP and CP do not represent free energy, which can be used for force generation, but only available source of this energy. It should be noted that G. Schwartz et al [122] observed a close correlation between the drop of segmentary contractility (by 24%) and the content of CP (r2=0.97), inorganic phosphate (Pi, r2=0"99) , and CP/ Pi ratio (r2=0.98) during the first few minutes of coronary occlusion. However, myocardial contractility under these conditions only little depended on ATP content: ATP utilized during systole (only 15% [105]) was rapidly resynthesized.…”
Section: Subcellular Mechanisms Of Hfmentioning
confidence: 93%
“…This phenomenon can be attributed to the fact that ATP and CP do not represent free energy, which can be used for force generation, but only available source of this energy. It should be noted that G. Schwartz et al [122] observed a close correlation between the drop of segmentary contractility (by 24%) and the content of CP (r2=0.97), inorganic phosphate (Pi, r2=0"99) , and CP/ Pi ratio (r2=0.98) during the first few minutes of coronary occlusion. However, myocardial contractility under these conditions only little depended on ATP content: ATP utilized during systole (only 15% [105]) was rapidly resynthesized.…”
Section: Subcellular Mechanisms Of Hfmentioning
confidence: 93%
“…Nonetheless, while it seems obvious that perturbation of cardiac energetics contributes to the failure of an oxygen-starved heart, the exact mechanisms underlying the decline in cardiac contractile function during oxygen deprivation remain equivocal despite decades of research (1,81). Some studies propose that depletion of high-energy phosphates [ATP and phosphocreatine (PCr)] and/or accumulation of metabolic by-products such as H ϩ , ADP, and inorganic phosphate (P i ) causes cardiac function to deteriorate (2,15,16,22,26,27,50,63,81). Others argue against such mechanisms (3,14,44,50,62).…”
mentioning
confidence: 99%
“…Some studies suggest that vascular collapse may be an important mediator of contractile depression after acute no-flow ischemia (29,30). However, other studies have demonstrated a close relationship between the initial fall of pressure and energy phosphate metabolites after acute noflow ischemia, suggesting that vascular collapse is not important in mediating contractile depression (31,32).…”
Section: Discussionmentioning
confidence: 99%